Systematic Review, Meta-analysis, and Network Meta-analysis of the Cardiovascular Safety of Macrolides - Gorelik, Einat; Masarwa, Reem; Perlman, Amichai; Rotshild, Victoria; Muszkat, Mordechai; Matok, Ilan (Antimicrobial agents and chemotherapy, 2018)
Studies reporting an increased risk for cardiac toxicities with macrolide antibiotics have raised concern regarding their cardiovascular safety. We sought to assess the cardiac safety of macrolide antibiotics as a class and of the individual agents by conducting a systematic review and network meta-analysis. Medline, Embase, and the Cochrane Library were searched up to February 2018 for studies reporting on cardiovascular outcomes with macrolides. We followed the PRISMA 2009 guidelines for data selection and extraction. Outcomes were pooled using random-effects models and odds ratios (OR), and 95% confidence intervals (CI) were calculated for arrhythmia, cardiovascular death, and myocardial infarction (MI). A total of 33 studies and data on 22,601,032 subjects were retrieved and included in the current meta-analyses. Macrolide use was not associated with the risk of arrhythmia or cardiovascular mortality. In the primary analysis, macrolide use was associated with a small but statistically significant 15% increase in risk for MI (OR = 1.15 [95% CI, 1.01 to 1.30]). In indirect network meta-analysis, erythromycin and clarithromycin were ranked considerably more likely to be associated with a higher risk for MI and significantly associated with increased risk of MI compared to azithromycin (OR = 1.58 [95% CI, 1.18 to 2.11] and OR = 1.41 [95% CI, 1.11 to 1.81], respectively). Our findings indicate that macrolide antibiotics as a group are associated with a significant risk for MI but not for arrhythmia and cardiovascular mortality. Among the macrolides, erythromycin and clarithromycin were associated with a greater risk of MI. However, it is possible that the association between macrolide use and risk of MI is the result of residual confounding.